G433(P) Associations between pre-injury impairment and thermal burn injury in children: analyses of the burns and scalds assessment template (basat) data. (12th March 2018) - Ikpeme, MJ; Emond, AM; Mytton, JA; Hollen, L
Abstract : Aim: A systematic review of published research on paediatric burn epidemiology in high income countries indicated a paucity of evidence regarding the association between pre-injury impairment in children and the risk of burn injuries. The aim of this study is to investigate differences in paediatric burn injuries by impairment status. Methods: The Burns and Scalds Assessment Template (BaSAT) was used in A and E departments in England and Wales to collect clinical and socio-demographical information on burn cases. From July 2012-November 2016, 2779 burn cases were recorded of which 1364 were suitable for inferential analyses. In this study, impairment was collated from parents/carers reports of what additional needs their children had (i.e. behavioural versus non-behavioural). The primary outcome was burn type (scalds versus non-scalds). Burn depth (full thickness (FT) versus non FT) and use of cold running water (CRW) first aid were secondary outcomes. Inferential analyses employed multivariable logistic regression in STATA v.14. Variables of interest were 90.1% to 100% complete. Unadjusted odds ratios (OR) and adjusted OR (AOR) were recorded with 95% confidence intervals (CI). Results: Compared to children with no impairment, children with behavioural (AOR=0.33 [95% CI: 0.03 to 3.35]) or non-behavioural (AOR=1.23 [95% CI: 0.32 to 4.35]) impairment were no more likely to suffer scalds than non-scalds. Furthermore, children with behavioural impairment (compared to non-impaired children) were more likely to have FT than non-FT burns (OR=8.33 [95% CI: 2.10 to 33.0]). This effect remained when adjusting for individual factors i.e. age and sex (AOR=5.76 [95% CI: 1.38 to 24.0]) but attenuated after adjusting for family (ethnicity, supervision levels, history of domestic violence in home and social workers) and environmental factors (IMD and location of burn event). Furthermore, children with behavioural impairment were less likely to have CRW first aid than those with no impairment (OR=0.26 [95% CI: 0.07 to 0.97]). This effect remained when individual and family factors were adjusted for (AOR=0.32 [95% CI: 0.11 to 0.88]). Conclusions: Children with impairment are not at more risk of having scalds compared to non-scalds; full thickness burns or lesser likelihood of having CRW first aid (after controlling for confounding factors) compared to children with no impairment. Acknowledgement: This project was sponsored by funds from the Scar Free Foundation, an NGO/charity involved in injury research.